Optimalisasi Pekerjaan Pemindahan Tanah Pada Proyek Embung Begawan Kota Tarakan Dengan Model Antrian - Setiawan, Budi; Hermanto, Hermanto (Borneo Engineering : Jurnal Teknik Sipil, 2017)
The Embung Bengawan Project in Tarakan City has several jobs requiring heavy equipment including mechanical soil removal activities. Activity of mechanical soil movement is a series in work of loading and transportation equipment. In order to achieve optimal mechanical soil removal targets, it is necessary to know the performance of the machine during the mechanical soil removal process. The optimization of production is the way to obtain production that is in accordance with optimal conditions of mechanical devices. This paper discusses the optimization of dump truck queue time and the number of dump trucks. Performance calculation tool using the method of production capacity of the tool, and calculate the optimal queue using the Queue Model method. Calculation using queuing model method obtained by result of time required by 3 excavator unit and with combined amount of dump truck will give result of cost equal to Rp 48,097,711 / day, and dump truck waiting time in queue to 1 minute. Then the optimal time is obtained by operating 3 units of excavators with a cost difference of Rp 3,572,826 / day from the real condition of the field that operates 2 excavator units